Truncation of LEAFY COTYLEDON1 Protein Is Required for Asexual Reproduction in Kalanchoë daigremontiana. Issue 1 (24th March 2014) - Garcês, Helena M.P.; Koenig, Daniel; Townsley, Brad T.; Kim, Minsung; Sinha, Neelima R.
Abstract : A mutated master regulator of zygotic embryogenesis is essential for creating somatic embryos and enhancing asexual propagation in Kalanchoë . Abstract: Kalanchoë daigremontiana reproduces asexually by generating numerous plantlets on its leaf margins. The formation of plantlets requires the somatic initiation of organogenic and embryogenic developmental programs in the leaves. However, unlike normal embryogenesis in seeds, leaf somatic embryogenesis bypasses seed dormancy to form viable plantlets. In Arabidopsis ( Arabidopsis thaliana ), seed dormancy and embryogenesis are initiated by the transcription factor LEAFY COTYLEDON1 ( LEC1 ). The K. daigremontiana ortholog of LEC1 is expressed during leaf somatic embryo development. However, KdLEC1 encodes for a LEC1-type protein that has a unique B domain, with 11 unique amino acids and a premature stop codon. Moreover, the truncated KdLEC1 protein is not functional in Arabidopsis. Here, we show that K. daigremontiana transgenic plants expressing a functional, chimeric KdLEC1 gene under the control of Arabidopsis LEC1 promoter caused several developmental defects to leaf somatic embryos, including seed dormancy characteristics. The dormant plantlets also behaved as typical dormant seeds. Transgenic plantlets accumulated oil bodies and responded to the abscisic acid biosynthesis inhibitor fluridone, which broke somatic-embryo dormancy and promoted their normal development. Our results indicate that having a mutated form of LEC1 gene in K. daigremontiana is essential to bypass dormancy in the leaf embryos and generate viable plantlets, suggesting that the loss of a functional LEC1 promotes viviparous leaf somatic embryos and thus enhances vegetative propagation in K. daigremontiana . Mutations resulting in truncated LEC1 proteins may have been of a selective advantage in creating somatic propagules, because such mutations occurred independently in several Kalanchoë species, which form plantlets constitutively.